Strategi Pendekatan Transformatif Dalam Mengembangkan Soft Skill Pemuda Gereja - Christina Anjani Makasihi; Heldy J. Rogahang; Olivia C. Wuwung (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aimed to develop soft skills of church youth through a transformative approach strategy. The method in this research uses qualitative methods. With data collection using observation techniques, interviews and documentation studies. So that it is found that it is important to use a transformative approach in developing soft skills for church youth so that they can train emotional intelligence and communication skills that can shape their soft skills so that every youth is able to adjust wherever they are with role models who can be a blessing